1985
DOI: 10.2500/108854185779109089
|View full text |Cite
|
Sign up to set email alerts
|

Marked Peripheral Eosinophilia: A Clue to Allergic Bronchopulmonary Aspergillosis in Office Practice

Abstract: Allergic Bronchopulmonary Aspergillosis (ABPA) is not rare. A diagnosis of "clinically probable ARPA" should be suspected in asthmatics who are not well controlled on adequate bronchodilators, who are steroid dependent or who have recurrent pulmonary infiltrates, and who also have a positive skin test with a separate aspergillus extract. Suspicion should also stimulate pursuit of this diagnosis in asthmatics with a total eosinophil count over 500 cellsl mm 3 or a total serum IgE level over 1,000 IUlm!. Early d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It was suggested that allergy cannot be used to predict eosinophilia in nasal mucosa. 13 Eosinophilia of the airway may be related not only to allergy but also infection, such as fungus 14,15 and rhinovirus 16 infections. Bachert et al 17 were able to show a strong local upregulation of the IgE synthesis with the formation of specific IgE to Staphylococcus aureus enterotoxins, suggesting a possible role of superantigens in the pathologic processes of NPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that allergy cannot be used to predict eosinophilia in nasal mucosa. 13 Eosinophilia of the airway may be related not only to allergy but also infection, such as fungus 14,15 and rhinovirus 16 infections. Bachert et al 17 were able to show a strong local upregulation of the IgE synthesis with the formation of specific IgE to Staphylococcus aureus enterotoxins, suggesting a possible role of superantigens in the pathologic processes of NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell counting was averaged and evaluated with scores from 0 to 3. 7,8 The counting was performed blindly without the investigator knowing the identity of the sample as follows: 0 ϭ no positively-stained cells, 1 ϭ few (1-10) positive cells, 2 ϭ moderate number (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of positive cells and some clusters of positive cells, and 3 ϭ many (Ͼ20) positive cells. For CD4ϩ and CD8ϩ cells, additional absolute cell counts were performed and a mean number of cell counts in 3 power fields were calculated.…”
Section: Cell Countingmentioning
confidence: 99%